Field notes contributed by Thomas H. Kent, November 27, 1996 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1996)
List of birds and locations contributed by Thomas H. Kent with observer Robert I. Cecil. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed